THE IMPACT OF THE GEOGEBRA PROGRAM ON IMPROVING THE LEARNING QUALITY OF 6TH GRADE STUDENTS IN TEACHING LINEAR INEQUALITIES - Aituar, А.; Keulimzhayeva, Ж.; Omarbayeva, Б. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
In this paper was considered the effect of the computer interactive program Geogebra on learners academic performance in teaching the system of linear algebraic inequalities. The research involved 30 learners from Mahatma Gandhi Specialized Lyceum no 92 in Almaty. Lessons in the experimental group were conducted using the Geogebra program, and the control group received on the traditional method of teaching. This research was conducted among 6th-class learners. During the research, learners from both groups were assessed pre and post tests, consequently learners in the experimental group showed significant improvement in academic performance compared to the control group (with an effect size of d = 0.819). In the end of the research, a survey was conducted among learners about the impact of the Geogebra program on learning outcomes. As a result of the research, the effect of the program Geogebra on learners academic performance in teaching the topic of "System of linear algebraic inequalities" was determined